Cardiac and vascular features of arterial and venous primary antiphospholipid syndrome. The multicenter ATHERO-APS study. Issue 209 (January 2022) - Bucci, Tommaso; Ames, Paul R.J.; Triggiani, Massimo; Parente, Roberta; Ciampa, Antonio; Pignatelli, Pasquale; Pastori, Daniele; ,
Abstract: Background: Patients with primary antiphospholipid syndrome (PAPS) may suffer from venous and/or arterial thrombosis, but studies addressing eventual clinical and laboratory features that may discriminate between arterial thromboembolism (ATE) from venous thromboembolism (VTE) have been poorly addressed. Methods: Cross sectional comparison of baseline characteristics of 100 patients enrolled in the multi center ATHERO-APS cohort study; patients with previous ATE and VTE were compared with regards to clinical and biochemical variables as well as to echocardiographic features and ankle-brachial index (ABI) measured at enrolment. Results: Mean age of patients was 51 years, 72 were women. 60 patients suffered VTE and 40 ATE. Compared to VTE, ATE patients displayed a higher prevalence of hypertension (43.3% vs. 65%, p = 0.034) and diabetes (3.3% vs. 17.5%, p = 0.015). Mean concentration of inflammation and complement activation markers were similar between the two groups as well as autoantibodies titres; mean D-dimer concentration was greater in VTE patients (184 ng/ml vs. 347 ng/ml; p = 0.024) whereas mean platelet count was greater in ATE patients (263 × 10 9 /L vs 216 × 10 9 /L, p = 0.044). By multivariable logistic regression analysis, adjusted for age, sex, hypertension and diabetes, ABI ≤ 0.9 (OR: 3.4; p = 0.041) and left atrial enlargement (OR: 3.5; p = 0.035) were associated with a history of ATE. ATE patients had a higher prevalence of ABI <0.9 (32.5% vs 10% p = 0.005) than VTE patients. At logistic regression analysis, IgG aCL >120 GPL U/ml was associated with an ABI ≤0.9 (OR: 5; p = 0.023) after adjustment for age and sex. Conclusion: Clinical, laboratory and cardiovascular variables distinguish arterial from venous APS patients, amongst which the ABI and left atrial enlargement. Implications for these two distinct clinical phenotypes of APS patients need further investigation. Highlights: Cardiovascular risk factors are frequent in PAPS patients with previous arterial thromboembolic events (ATE). Low ankle brachial index (ABI) and left atrium enlargement are frequent in PAPS and associated with ATE. Impaired right ventricular function correlates with previous venous thromboembolism in PAPS patients. Vascular doppler and echocardiography may identify distinct phenotypes of PAPS requiring tailored anti-thrombotic strategies